Isolation and characterisation of novel broadly neutralising antibodies from rabbits immunised with the HIV-1 Env/2dCD4S60C immune complex - Smith, Simone (My University, 2020)
Developing a safe and effective prophylactic vaccine against HIV-1 still remains the most effective strategy for controlling and eliminating the worldwide health burden of HIV infection. In order for an HIV-1 vaccine to be effective, it would need to elicit “long-lasting” broadly neutralizing antibody (bNAb) responses capable of providing protection against a large number of globally circulating HIV-1 subtypes. The development of effective vaccines by previous human clinical trials have failed to elicit protective immunity, and this may be due to the many challenges of HIV 1 vaccine design including the conformation-dependent exposure of critical epitopes in an immunogen. The viral envelope glycoprotein (Env; the target of bNAbs) binding to CD4 exposes epitopes which are masked in the unbound Env conformation, such as CD4 induced epitopes that are subsequently exposed during the open Env conformation. A preliminary study performed by our laboratory testing various HIV-1 Env/2dCD4S60C immune complexes in rabbit immunisations have demonstrated that it is possible to generate antibodies capable of neutralising tier-2 (harder to neutralise) HIV-1 pseudoviruses in vitro. The aim of this study was to delineate the neutralising responses observed in these Env/2dCD4S60C immunised rabbits by isolating and characterising the monoclonal antibodies from these sera. The first objective was to confirm the presence of neutralising antibody responses elicited by the immunized New Zealand white rabbits in response to a booster with the immunogen complex using the TZM-bl based neutralising assays. The trimeric gp140GCN4 and 2dCD4S60C were expressed, purified, and complexed for use in the rabbit booster immunizations. Next, we sought to sort for single antigen-specific memory B cells using a multi-parameter Flow Cytometry and Fluorescence Activated Cell Sorting (FACS) technique. Following single cell sorting, transcriptionally active linear expression cassettes (TAPs) were assembled by PCR. The linear cassettes containing a promoter, the antibodies variable and constant regions and a terminator sequence were assembled in a mammalian expression vector system as TAPs. Matched linear cassettes pairs (heavy- and light-chains) were co-transfected in HEK 293T mammalian cells and tissue culture supernatants were collected, concentrated and evaluated for monoclonal antibody expression. Concentrated culture supernatants were tested to determine the binding activity of the expressed antibodies, and confirm size and identity using ELISAs and SDS PAGE/western blot analyses, respectively. Using the TZM-bl neutralization assay, our results confirmed the persistence of circulating neutralizing antibody responses two years after the last v immunization (new baseline) against a heterologous, tier-2 clinically relevant pseudovirus, ZM53M.PB12. In addition, we demonstrated that these specific neutralization titres (ID50) could once again be elevated in three rabbits following a single boosting immunization with the Env/2dCD4S60C complex. Anti-HIV-1 specific B cells from rabbit PMBCs post booster were successfully isolated and sorted as single cells using multi-parameter Flow Cytometry and FACS techniques. All elements of the TAP cassette were successfully PCR amplified from the sorted B cells, however, subsequent analysis showed that the antibody variable fragments were missing from the assembled TAP cassettes. As such, the expressed proteins failed to bind the Env, 2dCD4S60C and Env/2dCD4S60C antigens in an ELISA, and the presence of truncated antibody fragments was confirmed in the immunoblot assays. Overall, the durability of the bNAb response elicited by immunization with the Env-2dCD4S60C complex were confirmed, highlighting the importance of isolating and characterizing the monoclonal antibodies responsible for neutralization, and future strategies can optimize the protocols described here
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, School of Molecular Medicine and Haematology, University of the Witwatersrand, Johannesburg, 2020